Agriculture in Africa – Telling Myths from Facts : A Synthesis - Christiaensen, Luc (Elsevier, 2018)
Stylized facts drive research agendas and policy debates. Yet robust stylized facts are hard to come by, and when available, often outdated. The 12 papers in this Special Issue revisit conventional wisdom on African agriculture and its farmers’ livelihoods using nationally representative surveys from the Living Standards Measurement Study-Integrated Surveys on Agriculture Initiative in six African countries. At times they simply confirm our common understanding of the topic. But they also throw up a number of surprises, redirecting policy debates while fine-tuning others. Overall, the project calls for more attention to checking and updating our common wisdom. This requires nationally representative data, and sufficient incentives among researchers and policymakers alike. Without well-grounded stylized facts, they can easily be profoundly misguided.